Temporary Work and Deviant Behavior the Role of Workplace Cohesion. Issue 4 (1st October 2020) - Akkerman, Agnes; Sluiter, Roderick; Jansen, Giedo
ABSTRACT: We investigate differences in deviant behavior between temporary workers and permanent workers and study the moderating role of workplace cohesion. We distinguish between task cohesion, which reflects the way colleagues work together as a team to complete tasks, and social cohesion, which reflects how well colleagues relate. We predict that task cohesion and social cohesion prompt norms on tolerating group members' deviant behavior and test our hypotheses on the Work and Politics 2016 data set, consisting of 787 Dutch employees. We find that temporary work does not lead to deviant behavior per se, but its effect on deviant behavior is moderated by workplace cohesion. We conclude that the distinction between task cohesion and social cohesion is crucial for understanding the effect of temporary work on deviant behavior.